Lanthanide luminescence as a local probe in mixed anionic hydrides – a case study on Eu2+-doped RbMgHxF3−x and KMgHxF3−x. Issue 47 (22nd November 2018) - Wylezich, Thomas; Welinski, Sacha; Hoelzel, Markus; Goldner, Philippe; Kunkel, Nathalie
Abstract : A case study on lanthanide luminescence as a local probe for the detection of hydride in salt-like mixed anionic hydrides. Abstract : In the search for novel mixed anionic hydrides, simple and sensitive detection methods can be useful and local probes lead to a better understanding of the materials. In our present study, we show that 5d–4f lanthanide luminescence can serve as a local sensor to verify the presence of hydride and potentially estimate the hydride content. As a model system, the Eu 2+ -doped hydride fluoride solid solution series of MMgD x F3− x (MMgH x F3− x ) with M = K, Rb is used, which were prepared and characterized by a combined X-ray and neutron diffraction approach. At room temperature, the compounds with M = Rb crystallize in a hexagonal perovskite-type structure and those with M = K crystallize in a normal cubic perovskite structure. Their lattice parameters follow Vegard's law. We also reinvestigated the structure and anion distribution in KMgD2 F. Bright yellow emission in RbMgH3 :Eu 2+ is observed for the first time and for both M, the hydride fluoride compounds show Eu 2+ emission energies between those of the pure hydrides and fluorides, which can be used for calibration and fast idendification of the hydride content, especially in the region of low hydride content.